Analisis Kelayakan Usaha Wedang Uwuh Oleh CV. Gunung Brujul Agung Makmur - Fatmawati, Nurlaila; Syafingi, Imam; Nugroho, Rahmat Joko (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The aim of this research is to analyze business feasibility from the financial and non-financial aspects of the CV Gunung Brujul Agung Makmur wedang uwuh business. The data analysis method used is qualitative (legal, marketing, technical, management and human resources and social and environmental aspects) and quantitative to analyze financial aspects through economic feasibility indicators, namely business income, Break Even Point (BEP) units, Break Even Point (BEP) price and Profit and Cost Ratio (R/C). The overall non-financial aspects are decent, except for the management aspects. The management and human resource aspects are not feasible because this business does not have good financial records and does not have an organizational structure. Financial analysis obtained income/year of Rp. 38,784,000 or analysis obtained income/month of Rp 3.232.000. BEP units 5760 pcs with a minimum unit of 121 pcs. BEP price is IDR 17,500 with a minimum price of IDR 12,433/pcs. R/C ratio value 24.2.